Factors influencing destination food image in Penang World Heritage Site - Ung, Ean Na (2016)
This study aims to investigate the relationship of destination food image has on the preference and intention to eat of Penang food among tourist. As Penang is well known for food tourism, it is important to identify the cognitive images that influence the preference and intention to eat specifically among tourists. The empirical objectives of this dissertation concerned identifying cognitive image of destination foods that influence on preferences for destination foods, influence on intention to eat destination foods and that behaviour intention is mediated by preference for destination foods. A survey using questionnaire was conducted among 151 tourists around the Penang World Heritage Site which is well known for its food tourism. Results indicated that the tourists has good cognitive image towards the Penang food except in promoting health. Attractiveness of Penang food was identified as the image that significantly influences both preference and intention to eat. This study has an impact in allowing to recognize the images such health promotion that needs to be given attention in order to improve the preference and intention to eat Penang Food.